Manajemen Persampahan di Kecamatan Rimbo Tengah Kabupaten Bungo - Zepa Anggraini; Joko Susanto (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2019)
The Bungo District Environmental Agency as the prime mover in responsible waste management and encourages the community to be involved in waste management, that waste problems in Rimbo Tengah Subdistrict Bungo Regency will not be solved if it only depends on the government alone, and therefore needs support and community participation in waste management. The purpose of this study was to determine waste management in the Rimbo Tengah District of Bungo Regency. The method used in this research is descriptive method with a qualitative approach. As for the informants in this study amounted to eight people consisting of five informants from the Bungo Regency Environmental Agency and three informants from the local community who are in Central Rimbo District. The data collection techniques are through observation, interviews and document review. The results showed that waste management in Rimbo Tengah Subdistrict, Bungo District, by the Bungo Regency Environmental Agency was well implemented. This can be seen from the application of management perspective which plays an important role in the whole process of waste management starting from planning, organizing, implementing / mobilizing and controlling. However, in the process of waste management by the Bungo Regency Environmental Agency, there are still some problems and shortcomings in the management process, namely the implementation or mobilization and supervision processes.